2018
DOI: 10.1590/0004-282x20180012
|View full text |Cite
|
Sign up to set email alerts
|

OxLDL plasma levels in patients with Alzheimer's disease

Abstract: The data analyzed together did not reveal significant differences in lipid profiles, including oxLDL levels. However, the importance of lipid changes in the genesis of the disease cannot be ruled out. Nevertheless, the ApoE ε4 allele was significantly more frequent in patients with Alzheimer's dementia in agreement with previous findings in the literature, but this genetic component did not change the levels of oxLDL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…Pretreatment with probiotics for six weeks before induction of AD by Aβ(1–42) was associated with significant changes in aforementioned biochemical parameters as compared to the sham group. However, Grossi et al (2018) did not report any significant differences in TC, high-density lipoprotein-cholesterol, or low-density lipoprotein-cholesterol levels between patients with AD and those without; however, in this study TG levels were reported to be lower in AD patients than controls. In addition, Akbari et al (2016) showed that treatment with probiotics for 12 weeks in patients with AD positively impacts cognitive function, but is not associated with any significant changes in lipid profiles.…”
Section: Discussioncontrasting
confidence: 89%
“…Pretreatment with probiotics for six weeks before induction of AD by Aβ(1–42) was associated with significant changes in aforementioned biochemical parameters as compared to the sham group. However, Grossi et al (2018) did not report any significant differences in TC, high-density lipoprotein-cholesterol, or low-density lipoprotein-cholesterol levels between patients with AD and those without; however, in this study TG levels were reported to be lower in AD patients than controls. In addition, Akbari et al (2016) showed that treatment with probiotics for 12 weeks in patients with AD positively impacts cognitive function, but is not associated with any significant changes in lipid profiles.…”
Section: Discussioncontrasting
confidence: 89%
“…There are studies that state that high levels of HDL-C are associated with a lower risk of AD, while the low levels of HDL-C are accompanied by hyperinsulinemia, which is a risk factor for the disease. In addition, cholesterol HDL is critical for the maturation of synapses, as well as maintaining synaptic plasticity, which influences Aβ clearance and the formation of neurofibrillary tangles that are directly linked to the development and evolution of AD stages (BUTTON et al, 2019;GROSSI et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, oxidation-derived stress in the CNS can lead to the oxidation of LDL-C (ox-LDL) and VLDL (ox-VLDL), which determine cytotoxicity of oxidized forms (Escargueil-Blanc et al, 1994). The incidence (Grossi et al, 2018) of the ε4-allele of the APOE gene is higher in AD patients than in controls, which indicates the importance of genetic factors in AD development.…”
Section: Dyslipidemia In Admentioning
confidence: 99%